Impact of inkjet printed ZnO electron transport layer on the characteristics of polymer solar cells. Issue 24 (9th April 2018) - Sánchez, José G.; Balderrama, Víctor S.; Garduño, Salvador I.; Osorio, Edith; Viterisi, Aurelien; Estrada, Magali; Ferré-Borrull, Josep; Pallarès, Josep; Marsal, Lluis F.
Abstract : In this paper, we demonstrate that zinc oxide (ZnO) layers deposited by inkjet printing (IJP) can be successfully applied to the low-temperature fabrication of efficient inverted polymer solar cells (i-PSCs). Abstract : In this paper, we demonstrate that zinc oxide (ZnO) layers deposited by inkjet printing (IJP) can be successfully applied to the low-temperature fabrication of efficient inverted polymer solar cells (i-PSCs). The effects of ZnO layers deposited by IJP as electron transport layer (ETL) on the performance of i-PSCs based on PTB7-Th:PC70 BM active layers are investigated. The morphology of the ZnO-IJP layers was analysed by AFM, and compared to that of ZnO layers deposited by different techniques. The study shows that the morphology of the ZnO underlayer has a dramatic effect on the band structure and non-geminate recombination kinetics of the active layer deposited on top of it. Charge carrier and transient photovoltage measurements show that non-geminate recombination is governed by deep trap states in devices made from ZnO-IJP while trapping is less significant for other types of ZnO. The power conversion efficiency of the devices made from ZnO-IJP is mostly limited by their slightly lower J SC, resulting from non-optimum photon conversion efficiency in the visible part of the solar spectrum. Despite these minor limitations their J – V characteristics compare very favourably with that of devices made from ZnO layer deposited using different techniques.